Religious Moderation Education as a Means to Prevent Bullying in Schools - Syafii, Imam; Harjanto, Muhammad Alfian Dusan; Purnomo; Izzudin Syifaulhanani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study aims to examine the role of religious moderation education in preventing bullying in schools. A qualitative approach was used, employing observation techniques at a vocational school in Central Java. The study focused on the concept of religious moderation within the school, the learning process, and the integration of moderate values, mindsets, and attitudes. Data were collected through interviews with six respondents, including the school principal, two guidance counselors, an Islamic education teacher, two students, and from school documents such as annual activity reports and teaching modules. Data analysis was conducted qualitatively, using triangulation of sources and techniques, which involved comparing and validating data from various sources (school principal, guidance counselors, Islamic education teacher, students) and school documents to ensure the validity and consistency of the findings. The results of the study reveal that the strategy of instilling religious moderation was implemented through teacher role modeling, the integration of values such as tolerance, justice, and anti-violence in lessons, daily religious activities, student empowerment as agents of change through the Roots Indonesia program, and cross-curricular collaboration. This strategy contributed to creating an inclusive school climate and significantly reduced incidents of verbal bullying. The findings indicate that the implementation of religious moderation values in school education is effective in reducing bullying behaviors and fostering a more inclusive, tolerant, and diverse learning environment.